IMPROVING READING SKILLS IN THE USE OF QUESTION AND ANSWER - Zainuddin Zainuddin (Journal of English for Academic and Specific Purposes, 2020)
This paper discusses the nature of reading comprehension, types of comprehension, why questioning helps students comprehend texts better. It also correlates to the advantages of using Questions-Answer Relationship (QAR) to improve students’ reading comprehension skills and the application of QAR. the paper concludes with several suggestions for classroom in the university level. This research was planned for collaborative classroom activity where the writer (acted as the instructor) and his collaborator (acted as the observer) worked together on the methods of this research, specifically: preparatory, planning, actualizing the plan, observing the activity, and reflecting the result of the activity. The subjects of this research were 30 English students at English education department in the university. For the data collection, the writer employed the checklist, field notes, and test. All the data collection were analyzed descriptively, and the results were compared with the criteria of success in this article to see whether the criteria of success had been accomplished or not.